2007
DOI: 10.1111/j.1600-0625.2007.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Human S100A15 splice variants are differentially expressed in inflammatory skin diseases and regulated through Th1 cytokines and calcium

Abstract: The human calcium-binding protein (hS100A15) was first identified in inflamed hyperplastic psoriatic skin, where the S100A15 gene is transcribed into two mRNA splice variants, hS100A15-S and hS100A15-L. To compare the contribution of the human S100A15 (hS100A15) isoforms in skin inflammation and differentiation, we determined the expression, distribution and regulation of hS100A15-S and hS100A15-L in psoriasis and chronic atopic eczema compared with normal skin. We found that both hS100A15 transcripts were mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 30 publications
7
42
0
Order By: Relevance
“…They act as proinflammatory danger molecules 'alarmins' on keratinocytes and as chemoattractants for leukocytes to potentiate inflammation in the skin. Overexpressed in psoriatic lesions, they synergize through their distinct expression and functional mechanisms and contribute to the development of skin lesions [10][11][12][13][14][15]. In the present study we investigated the expression of koebnerisin and psoriasin in human Here, we demonstrated for the first time that koebnerisin and psoriasin were expressed by human leukocytes from peripheral blood showing cell type-specific expression patterns.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…They act as proinflammatory danger molecules 'alarmins' on keratinocytes and as chemoattractants for leukocytes to potentiate inflammation in the skin. Overexpressed in psoriatic lesions, they synergize through their distinct expression and functional mechanisms and contribute to the development of skin lesions [10][11][12][13][14][15]. In the present study we investigated the expression of koebnerisin and psoriasin in human Here, we demonstrated for the first time that koebnerisin and psoriasin were expressed by human leukocytes from peripheral blood showing cell type-specific expression patterns.…”
Section: Discussionmentioning
confidence: 90%
“…3E-G). Data suggest that circulating, migratory leukocytes may contribute to the increased levels of koebnerisin and psoriasin observed in both skin lesions and in serum of patients with psoriasis [14,15,23].…”
Section: 3mentioning
confidence: 97%
See 2 more Smart Citations
“…We chose to analyze the S100 A6 and A4 subtypes in this study because we had observed variability in their expression in dendritic-appearing dermal cells incidentally during the course of an unrelated study, and some evidence suggests S100 proteins are involved in PSO [29][30][31] and that their expression may differ among PSO, normalappearing skin, and other inflammatory conditions including contact dermatitis. 32,33 Although the values approached significance, S100A6 1 cells were not significantly different between PSO and normalappearing skin or between ND and normalappearing skin.…”
Section: Discussionmentioning
confidence: 99%